2016
DOI: 10.1002/joc.4887
|View full text |Cite
|
Sign up to set email alerts
|

Accessing vulnerability of land‐cover types to climate change using physical scaling downscaling model

Abstract: The objective of this study is to investigate the vulnerability of different land-cover types to climate change. To this end, land-cover specific temperature change factors are quantified for the southern Saskatchewan region using a novel statistical downscaling model: physical scaling (SP). SP model considers large-scale climate and regional physical characteristics like land-cover, elevation in its formulation and hence can be used to predict future temperature for different land-cover types under changing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Several studies have found significant impact of land use and global climate change on hydroclimatic variables across the globe, e.g., in India (Singh et al, 2016); USA (Mallakpour & Villarini, 2015; Villarini et al, 2009) and Canada (Buttle, 2011; Gaur & Simonovic, 2017; Kerkhoven & Gan, 2013; Tan & Gan, 2015), highlighted the importance of nonstationary frequency analysis. Following that several studies have examined the validity of the stationary assumption in AM flood extremes and performed nonstationary flood frequency analyses across Canada (Cunderlik & Burn, 2003; Gado & Nguyen, 2016; Leclerc & Ouarda, 2007; Tan & Gan, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have found significant impact of land use and global climate change on hydroclimatic variables across the globe, e.g., in India (Singh et al, 2016); USA (Mallakpour & Villarini, 2015; Villarini et al, 2009) and Canada (Buttle, 2011; Gaur & Simonovic, 2017; Kerkhoven & Gan, 2013; Tan & Gan, 2015), highlighted the importance of nonstationary frequency analysis. Following that several studies have examined the validity of the stationary assumption in AM flood extremes and performed nonstationary flood frequency analyses across Canada (Cunderlik & Burn, 2003; Gado & Nguyen, 2016; Leclerc & Ouarda, 2007; Tan & Gan, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, we do not have global subkilometer in situ or satellite observational capabilities from which to derive these forcing variables. Therefore, physical, dynamic, and statistical downscaling approaches have been developed that interpolate the required high-resolution fields from coarser-resolution data incorporating the interactions between the atmosphere and terrestrial surface (Cosgrove et al 2003;Haylock et al 2006;Liston and Elder 2006;Girotto et al 2014;Sunyer et al 2015;Gaur and Simonovic 2017). For precipitation downscaling, Venugopal et al (1999) proposed dynamic space-time scaling of rainfall along with a spatial disaggregation scheme at subgrid scales.…”
Section: Introductionmentioning
confidence: 99%
“…Before estimating future urban temperatures, the Global Climate Model (GCM) simulation under Shared Socioeconomic Pathways (SSPs) needed to be scaled down to a finer resolution to provide accurate and localized projections. The dynamic downscaling methods have been commonly used to explore future urban-rural temperature differences [30][31][32][33][34]. However, previous studies using such a method only focused on representative Global Climate Model (GCM) projections and selected cities for projecting UHI effects instead of UCI [35][36][37].…”
Section: Introductionmentioning
confidence: 99%